The Role of University Students in Preventing Corruption in the Digital Era - Jajuli, Ahmad; Nurtresna, Robby (SEAN Institute, 2025)
From year to year, the intensity of corruption issues has increased. In the effort to eradicate corruption, university students play a strategic role by contributing to concrete activities, including mapping corruption and providing advocacy for corruption victims. The endeavor to prevent the proliferation of corrupt practices must be carried out by all elements of society, including the youth. History has recorded in golden ink the struggle of students in combating injustice. It is also noted that the nation’s struggle cannot be separated from the involvement of university students, and from their movements emerge prominent figures and national leaders. The student struggle is far from over. Today, students face challenges that are no less significant than those of the past—a situation that has left the nation in decline, exemplified by the rampant issue of corruption. Students must recognize that corruption is the principal enemy of the Indonesian nation and must be fought.